Mathematical Problem-Solving Ability in terms of Learning Independence in Problem Based Learning with E-scaffolding. (Universitas Negeri Semarang, 2022)
This study aims to describe the ability to solve mathematical problems in terms of independent learning of students in learning Problem Based Learning with e-scaffolding. The method used in this study was a qualitative method with 36 research subjects in class X IPS 5 at SMA Negeri 1 Lasem in the 2021/2022 academic year. Retrieval of data using independent learning questionnaires, test problem solving abilities and interviews. Data were analyzed descriptively through data reduction, data display, and triangulation. The results of the study show that (1) students with high learning independence have high and moderate mathematical problem solving abilities; (2) students with moderate learning independence have high, medium, and low problem solving abilities; (3) students with low learning independence have moderate and low mathematical problem solving abilities.